Козацький цвинтар у Чигирині: поховальний обряд, антропологія, археологічний матеріал. (Zaporizhzhia Historical Review, 2021)
The article dwells upon the remnants of Cossack cemetery of the XVI-XVII centuries discovered while performing protective archeological research in Chygyryn in 1989-1994. It is proved that investigating the materials discovered gives possibility to trace the character of material and spiritual culture development of ancient population of Ukraine in the end of XVI – middle of XVIIth centuries.